Pembuatan Cuka Ekstrak Jagung (Zea Mays) Dengan Menggunakan Acetobacter Aceti Dan Saccharomyces Cerevisiae - Agtavia, Velma; Thalib, Moh Randy Putra Preatama; Hasan, Ani M; Uno, Wirnangsi D; Botutihe, Lisnawati (Jurnal Pendidikan, Sains Dan Teknologi, 2025)
This study aims to produce natural vinegar from corn extract (Zea mays L.) through a two-stage fermentation process: alcoholic fermentation using Saccharomyces cerevisiae followed by acetic acid fermentation using Acetobacter aceti. The evaluation included physical observation, pH measurement, lactic acid bacteria (LAB) testing, organoleptic assessment, and determination of acetic acid concentration through titration. The results indicated notable physical changes during fermentation, with pH decreasing from approximately 7 to 6 over 7–14 days, accompanied by the emergence of a distinctive vinegar aroma that signified acetic acid formation. LAB activity was confirmed by colony growth on Nutrient Agar (NA) media, demonstrating their role in establishing an acidic environment favorable for the second fermentation stage. Overall, the findings show that corn extract has strong potential as a fermentation substrate for natural vinegar production using a biological process.